Investigation of tomato ringspot virus (ToRSV) by Real-Time TaqMan RT-PCR in Hakkari province, Turkey - Nevin Akdura; Murat Şevik (Journal of Agricultural Sciences)
Tomato ringspot virus (ToRSV) belongs to the Nepovirus genus in the family Secoviridae. It has a wide host range and is listed as a quarantine virus in Turkey. In this study, 80 leaf samples were collected from tomato, pepper, cucumber and grapevine cultivation sites located in three different parts of Hakkari province: Şemdinli, Çukurca and Center districts. Real-time TaqMan reverse transcription-polymerase chain reaction (RT-PCR) method was used for the detection of the virus. Amplification was carried out in reaction mix including QuantiNova Probe RT-PCR kit (Qiagen, Germany) using primers and TaqMan probe based on 3'-UTR (untranslated region) of virus, which amplified a 182 bp product of the genome. ToRSV was detected in 13 of the 80 samples and threshold cycle (CT) values ranged from 23.9 to 37.4. It was found that 16.25% of the samples collected from the districts of Hakkari province were found to be infected with ToRSV whereas no ToRSV was detected in the samples collected from the center of the city. The virus was detected on pepper and cucumber samples in Çukurca district, and it was also detected in tomato, pepper, cucumber and grapevine samples in Şemdinli district. To our knowledge, this study is the first report of molecular detection of ToRSV by real-time TaqMan RT-PCR in Turkey.